Reaching early adolescents with a complex intervention for HIV prevention: findings from a cohort study to evaluate DREAMS in two informal settlements in Nairobi, Kenya - Sarah Mulwa; Jane Osindo; Elvis O. Wambiya; Annabelle Gourlay; Beatrice W. Maina; Benedict O. Orindi; Sian Floyd; Abdhalah Ziraba; Isolde Birdthistle (BMC, 2021)
Abstract Background The DREAMS Partnership promotes combination HIV prevention among adolescent girls and young women. We examined the extent to which DREAMS interventions reached early adolescent girls (EAG; aged 10-14 years) in two informal settlements in Nairobi, and the characteristics of those reached, after 3 years of implementation. Methods We utilized three data rounds from a randomly-sampled cohort of EAG established in 2017 in Korogocho and Viwandani informal settlements where DREAMS interventions were implemented. Interventions were classified as individual or contextual-level, with individual interventions further categorised as primary (prioritised for this age group), or secondary. We summarised self-reported invitation to participate in DREAMS, and uptake of eight interventions that were supported by DREAMS, during 2017-2019. Multivariable logistic regression analysis was used to identify individual and household characteristics associated with invitation to DREAMS and uptake of primary interventions. Results Data were available for 606, 516 (retention rate of 85%) and 494 (82%) EAG in 2017, 2018 and 2019, respectively. Proportions invited to DREAMS increased from 49% in 2017, to 77% by 2018, and to 88% by 2019. School-based HIV and violence prevention, and HIV testing and counselling were the most accessed interventions (both at 82%). Cumulative uptake of interventions was higher among those invited to participate in DREAMS compared to those never invited, particularly for new interventions such as social asset building and financial capability training. Contextual-level interventions were accessed infrequently. Most of those invited both in 2017 and 2018 accessed ≥3 interventions (96%), and 55% received all three primary interventions by 2019. Conclusions Uptake of DREAMS interventions among a representative sample of EAG was high and quickly increased over the implementation period. The majority accessed multiple interventions, indicating that it is feasible to integrate and deliver a package of interventions to EAG in a challenging informal context.